The artist as user and designer. (1st January 2013) - Lesage, Frédérik
Artists engaged in collective experiments with new information and communication technologies (ICTs) in collaboration with engineers and other computer scientists face a particular challenge: how to maintain 'creative control' over the collective process of experimentation without the technical and procedural expertise familiar to computing experts. This paper is an attempt to critically examine the artist's role as a creative individual and to better understand how he or she articulates this role as a designer and/or user of ICT infrastructures in order to develop relations of power in interdisciplinary collaborations. A conceptual and methodological framework based on the production of culture tradition and artistic careers is proposed in order to examine specific discourses articulated by artists as part of collaborative practices with ICTs followed by an empirical examination based on this approach. Based on the findings presented in this paper, I argue that artists working in this context are able to articulate certain forms of creative control through practices that do not directly relate to the production of artworks.